Bimultiplications and Annihilators of Crossed Modules in Associative Algebras - Ummahan Ege Arslan; Serdar Hürmetli (Journal of New Theory, 2021)
In this paper, we present a generalization of the concept of the bimultiplication algebra by defining the bimultiplication of crossed modules in associative algebras. Using this structure, we construct the actor of a crossed module in associative algebras, and we obtain annihilators of crossed modules as the kernel of a crossed module morphism from a crossed module to its actor. Moreover, we construct a link between this morphism and a crossed square, two-dimensional crossed module.